Modelling adhesive using non-linear truss elements in Mode I delamination problems : Modeliranje ljepila koristeći nelinearne štapne elemente kod problema raslojavanja u Modu I - Ranjbar, Maedeh (Array, 2020)
A fast and simple finite element model is presented in this paper to simulate the crack propagation in notched beam structures with two layers and one interface medium in Mode I delamination. The truss elements from FEAP element library are endowed with a user material law describing the bilinear cohesive zone model (CZM) with the material unloading path defined by embedding a history variable in the response. The layer is modelled with linear elastic Timoshenko beam elements. The method is used for damage growth and damage propagation simulations in interfaces with both ductile and brittle materials. The method is robust for ductile interfaces, but for brittle interfaces more specific numerical techniques are required. The results are evaluated using available analytical and numerical solutions and a good agreement is achieved.